Perbandingan Konsep Syibhul ‘Iddah dalam KHI dan Surat Edaran Dirjen Bimas Islam Perspektif Maqāṣid Syarī’ah - Pramana, Deky; Pancasilawati, Abnan; Andar Yuni, Lilik (Maqasid: Jurnal Studi Hukum Islam, 2024)
Reform and updating of Islamic family law are crucial aspects in realizing the benevolent teachings of Islam across different times and places, especially in addressing the issue of post-revocable divorce ('iddah) to ensure women's rights. One area undergoing reform in Indonesian family law is the implementation of the concept of syibhul 'iddah. This concept, adopted from the thoughts of Wahbah az-Zuḥaīlī, mandates a similar 'iddah for husbands, prohibiting them from marrying during their wives' 'iddah, both to women who are considered mahrams to the newly divorced wife and to other women for men who have just divorced one of their four wives. However, in Indonesia, there are two concepts of syibhul 'iddah enforced, namely under Article 41 and 42 of the Compilation of Islamic Law (KHI) and Circular Letter No. P-005/DJ.III/HK.007/10/2021. Although both concepts originate from the thoughts of Wahbah az-Zuḥaīlī, differences exist in their implementation within the Office of Religious Affairs (KUA) settings. Therefore, this research aims to compare the two concepts. This study employs a qualitative approach by comparing the concepts of syibhul 'iddah in KHI and the Circular Letter, viewed from the perspective of Maqāṣid al-Sharī'ah by Ibnu 'Asyūr. The research findings indicate a significant difference between the two concepts lies in the restriction on marriage for men during their wives' 'iddah. The prohibition in the Circular Letter is absolute, while in KHI, it is conditional. In the analysis of Maqāṣid al-Sharī'ah by Ibnu 'Asyūr, both concepts of syibhul 'iddah in KHI and the Circular Letter meet the criteria of maqāṣid al-khāṣah. However, concerning the criteria of maqāṣid al-'āmah, the Circular Letter concept does not meet the requirements of al-tsubūt and al-ẓuhūr. Keywords: Syibhul 'Iddah, KHI, Circular Letter, Maqāṣid al-Sharī'ah